1994
DOI: 10.1093/jnci/86.9.717
|View full text |Cite
|
Sign up to set email alerts
|

Sector Resection With or Without Postoperative Radiotherapy for Stage I Breast Cancer: Five-Year Results of a Randomized Trial

Abstract: The increase in recurrence rate observed over time suggests that surgical technique and patient selection should be improved. The benefits of reduced cost and patient inconvenience that would result from the elimination of postoperative radiotherapy must be carefully weighed against the disadvantages of local recurrence. Longer term follow-up must be done to estimate the risk of cancer recurrence in these women 10 and 15 years later, and methods must be developed to identify those women who have a higher risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
96
0
9

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(107 citation statements)
references
References 0 publications
2
96
0
9
Order By: Relevance
“…Small tumour size, low grade and old age have been proposed as selection criteria for patients who might not benefit from radiotherapy (Clark et al, 1992;Veronesi et al, 1993;Liljegren et al, 1994). However, in a highly selected group of 87 patients treated with breast-conserving surgery without radiotherapy, the rate of local recurrence rose to 16% when the median follow-up time was 56 months, therefore this prospective clinical trial was closed .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small tumour size, low grade and old age have been proposed as selection criteria for patients who might not benefit from radiotherapy (Clark et al, 1992;Veronesi et al, 1993;Liljegren et al, 1994). However, in a highly selected group of 87 patients treated with breast-conserving surgery without radiotherapy, the rate of local recurrence rose to 16% when the median follow-up time was 56 months, therefore this prospective clinical trial was closed .…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to investigate optional or additional treatment modalities such as more effective systemic therapies for women with a risk of local recurrence after limited surgery and irradiation (Gelber and Goldhirsch, 1994). Attempts have also been made to find a subgroup of low-risk patients who do not need radiotherapy (Clark et al, 1992;Veronesi et al, 1993;Liljegren et al, 1994).…”
mentioning
confidence: 99%
“…Although mastectomy and BCS (with follow-up radiation therapy) have equivalent outcomes (breast carcinoma recurrence rates, survival rates) for treating early-stage breast carcinoma, BCS without follow-up radiation therapy has an increased risk of breast carcinoma recurrence [5][6][7][8][9][10][11] and mortality. 12 Results of studies on racial differences in the use of BCS are inconsistent.…”
mentioning
confidence: 99%
“…9 -11 Several studies have shown that the majority of in-breast disease recurrences occur in the immediate vicinity of the lumpectomy cavity. [12][13][14][15] Disease recurrences elsewhere in the breast are found with extended follow-up in only 1-3% of patients. [12][13][14] These data suggest that the impact of whole breast RT on reducing the in-breast recurrence rate is limited to the site of initial involvement.…”
mentioning
confidence: 99%